Analysis Of The Preparation Of Financial Reports For Micro, Small And Medium Enterprises In The Boiler Chicken Farming Business In Sampe Cita Village Based On The Emkm Sak - Bukit, Kezia Evangglin; Chrisna, Heriyati; Franita, Riska (Universitas Dehasen Bengkulu, 2025)
This study aims to provide an overview of the preparation of financial reports by broiler chicken farms based on their compliance with accounting principles and to explain their sources of capital and financial performance. The object of this study is Muhtar Keliat's broiler chicken farm, which operated from February to November 2024. This is a descriptive quantitative study using a case study approach. Data collection was conducted through documentation and analysis of financial reports. The results indicate that the financial reports have been prepared in a simple manner but do not fully comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The business capital is entirely sourced from the owner, with no loans or liabilities. Profit and asset information have been recorded, but cash flow statements and notes to the financial statements have not been included. Challenges encountered in preparing the reports include a lack of accounting understanding and the lack of ongoing guidance in preparing standard-compliant financial reports. This impacts business owners' limited ability to use financial reports as a basis for optimal decision-making.